Supersymmetry and R-symmetry breaking in models with non-canonical Kähler potential - Aldrovandi, León Gabriel (2008)
We analyze several aspects of R-symmetry and supersymmetry breaking in generalized O'Raifeartaigh models with non-canonical Kähler potential. Some conditions on the Kähler potential are derived in order for the non-supersymmetric vacua to be degenerate. We calculate the Coleman-Weinberg (CW) effective potential for general quiral non-linear sigma models and then study the 1-loop quantum corrections to the pseudo-moduli space. For R-symmetric models, the quadratic dependence of the CW potential with the ultraviolet cutoff scale disappears. We also show that the conditions for R-symmetry breaking are independent of this scale and remain unchanged with respect to those of canonical models. This is, R-symmetry can be broken when generic R-charge assignments to the fields are made, while it remains unbroken when only fields with R-charge 0 and 2 are present. We further show that these models can keep the runaway behavior of their canonical counterparts and also new runaway directions can be induced. Due to the runaway directions, the non-supersymmetric vacua is metastable.